The reduction mechanism of copper molybdate at nonisothermal conditions - Kirakosyan, H. V. («Գիտություն» հրատ.)
The mechanism of interaction in the CuMoO4-xMg-yC system was studied at low and high heating rates by thermal analysis technique to reveal the reduction pathway of the copper molybdate by combined Mg/C reducing agents. According to the obtained results, the process initiates directly from the salt reduction and proceeds in two successive stages, first is a low and second is a strong exothermic interaction. Moreover, depending on the heating rate, a merging of different stages can be observed. The effective activation energy of the magnesiothermic reduction reaction for the CuMoO4+1.2Mg+2.2C mixture was calculated to be 199.5 ± 7.2 kJ/mol. Ուսումնասիրվել է պղնձի մոլիբդատի վերականգնման մեխանիզմը CuMoO4-xMg-yC համակարգում ջերմային անալիզի եղանակով տաքացան արագությունների լայն տիրույթում: Ըստ ստացված արդյունքների մոլիբդատի վերականգնումը տեղի է ունենում անմիջապես աղից, իրար հաջորդող երկու փուլերով․ առաջինը՝ թույլ, իսկ երկրորդը ուժեղ էկզոթերմ փոխազդեցությամբ։ Տաքացման արագության մեծացմանը զուգընթաց դիտվում է նշված փուլերի միաձուլում։ Որոշվել է CuMoO4+1.2Mg+2.2C խառնուրդում մագնեզիումաթերմ վերականգնման փուլի ակտիվացման էներգիան. E=199․5՞7․2 կՋ/մոլ։ В работе изучен механизм взаимодействия в системе CuMoO4-xMg-yC в широком диапазоне скоростей нагрева методом термического анализа с целью выявления последовательности превращений при восстановления молибдата меди с помощью комбинированных восстановителей Mg/C. Согласно полученным результатам установлено, что восстановление молибдата меди начинается с образования различных молибдатов с низким содержанием меди без предварительного разложения на оксиды в две последовательные стадии: первая – слабое, а вторая – сильное экзотермическое взаимодействие. При этом с повышением скорости нагрева имеет место перекрывание упомянутых стадий. Рассчитана энергия активации стадии магнезиотермического восстановления для смеси CuMoO4+1.2Mg+2.2C: Е=199,5 ± 7,2 кДж/моль․
Keywords: Inorganic chemistry; Physical Chemistry